A comparison of the information seeking behavior of physics and anthropology students at the University of the Philippines - Sison, Jennifer P.; Gonzales, Grace Marie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2003)
Differences in information need and information seeking behavior exist within user communities. In order to meet the information needs of the user community, information professionals must first understand the nature of the user community and become familiar with the information seeking habits and practices of the user.
This study was made to address whether there are significant differences in the information seeking behavior of students from different disciplines (i.e., students from Social Science disciplines and Pure Science disciplines). This study was designed to investigate patterns of research and information seeking practices of UP senior and junior students in Physics and Anthropology. The main purpose was to obtain a better understanding both of their information needs, preferences, and practices; the use of new information technologies; and their perceptions of the university/academic library capacity to meet these information needs. It also aimed to identify how these factors affect the differences in information seeking behavior between these two disciplines. The specific objectives are:1. To identify the information seeking behaviors of students in BS Physics and BS Anthropology in UP Diliman.2. To know if there are significant differences in information seeking behaviors by gender and by disciplines.3. To give possible recommendations for the improvement of their academic library in order to meet both their information
A comprehensive questionnaire patterned after Magday's (1986) survey questionnaire was used. It consists of three parts: 1) Personal Data (includes personal information of the respondent, i.e., course, gender, year level and number of major units taken in their field; 2) Use of Libraries (discusses the library usage of the students); and 3) Students' information seeking pattern (seeks to elicit responses that would determine the respondent's information seeking behavior pattern).A total of 98 questionnaires were distributed to 46 Anthropology majors and 52 Physics majors enrolled during the previous semester of the academic year 2002-2003 in University of the Philippines Diliman.
The findings of the study positively confirmed the hypotheses professed in Chapter 1. Therefore, the following conclusions were formulated: 1. User's needs for certain types of information are very much related to the role and functions they perform in their organization and society and that is being undergraduate students.2. The information seeking behavior of the scientists, as the Physics majors, and social scientists, as the Anthropology majors, as revealed by the results of this user study, do not show any great differences. Both scientists and social scientists use the same information sources and same methods in information retrieval. What is important is the degree of use which accounts for the differences in the information seeking behavior of scientists and social scientists.
To achieve a high degree of library use and satisfaction in the use of academic library, its resources and facilities, the researcher presents the following recommendations based on the results of the investigation: 1.A copy of this study should be furnished to the management of the UP Main Library, Anthropology Library and UP College of Science Library for further study towards a review of the library programs and policies necessary to suit the ever increasing demands of the users.2. Additional budget for the library is recommended and additional local support is definitely needed to maintain adequate services for the students.3. One major finding of the study is seemingly the independency of most of the respondents to the librarian as an information manager. It thus recommended that the librarians should be more approachable and aware of the needs of the users after all, they play a leading role in the dissemination of vital information for the task performance of their users, people whose work provide very important inputs to decision making.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman -- Students; Library use studies -- Philippines -- Quezon Citiy